Application of water quality indices and geostatistical methods for analyzing mountain lakes in relation to anthropogenic influences and catchment features: a case study in East Sikkim, India - Nilabhra Auddy; Rupa Sinha; Santasmita Das Bhattacharya; Krishnendu Kumar Pobi; Subhankar Dutta; Sumanta Nayek (Water Practice and Technology, 2023)
Water quality, pollution level, and trophic conditions were assessed in Aritar Lake located in the Himalayas in East Sikkim, India, in relation to geo-environmental influences and anthropogenic activity in its catchment. A comprehensive method involving indexing and multivariate analyses was used. Geostatistical tools were employed to interpolate seasonal and spatial deviations in water quality, and nutrient and organic load distribution. Lake water nutrient index (NI) values were between 4.61 and 7.31, and 2.65 and 4.69 during pre- and post-monsoon seasons, respectively, indicating significant nutrient enrichment and eutrophic conditions. For both seasons, the estimated organic pollution index (OPI) showed class II contamination (contamination starting), with post-monsoon values being higher. The study shows clear signs of eutrophication and early organic pollution. Effective management plans and sustainable tourism practices may benefit the lake, by reducing contamination and protecting the integrity of its ecosystem. HIGHLIGHTS Assessment of nutrient dynamics, organic pollution, and trophic state of the lake on a spatio-temporal scale.; Appraisal of water quality and lake health using the WQI, OPI, and geostatistical methods.; Multivariate analysis to delineate influencing factors and pollution sources.;